Emotional Labor, Occupational Identity, and Work Engagement among Portuguese First Responders - Soraia A. de Sousa Oliveira; Carla M. Santos de Carvalho; Ana L. Sousa Pinto; Sonia M. Guedes Gondim (Journal of Work and Organizational Psychology)

(untitled)
First responders, including police officers and firefighters, face emotionally intense, high-risk situations, necessitating effective emotional management to sustain work engagement and occupational identity. This study, grounded in emotional labor and social identity theories, analyzed data from 248 first responders to explore the impact of emotional labor on work engagement, with occupational identity as a mediator. Results showed that firefighters faced higher demands for positive emotion expression and reported greater occupational identity and work engagement than police officers. Positive emotion expression enhanced work engagement, while surface-acting and negative emotion suppression negatively affected both outcomes, particularly for police officers. Mediation analysis revealed occupational identity as a key mechanism linking emotional labor to work engagement. These findings highlight the stabilizing role of occupational identity in work engagement despite emotional labor demands. The study emphasizes the need for targeted and occupation-specific interventions among first responders to mitigate emotional exhaustion and sustain engagement.